Genomic and epidemiological surveillance of Zika virus in the Amazon region - Giovanetti, M; Faria, NR; Lourenco, J; Goes de Jesus, J; Xavier, J; Claro, IM; Kraemer, MUG; Fonseca, V; Dellicour, S; Theze, J; da Silva Salles, F; Graef, T; et al. (Cell Press, 2020)
Zika virus (ZIKV) has caused an explosive epidemic linked to severe clinical outcomes in the Americas. Until June 2018, 4,929 ZIKV suspected infections and 46 congenital syndrome cases were reported in Manaus city, Amazonas State, Brazil. Although Manaus is a key demographic hub in the Amazon region, little is known about the ZIKV epidemic there, both in terms of transmission and viral genetic diversity. Using portable virus genome sequencing we generated 59 ZIKV genomes in Manaus. Phylogenetic analyses indicated multiple introductions of ZIKV from northeast Brazil to Manaus. Spatial genomic analysis of virus movement among 6 areas in Manaus suggested that populous northern neighborhoods acted as sources of virus transmission to other neighborhoods. Our study revealed how the ZIKV epidemic was ignited and maintained within the largest urban metropolis in the Amazon. Those results might contribute to improve public health response to outbreaks in Brazil.